HISTORIOGRAPHY OF MIDDLE EAST HISTORY: A Journey of Truth-Seeking Amid Cultural and Political Diversity - Muttaqin, Mohammad Izdiyan (TARIKHUNA: JURNAL SEJARAH PERADABAN ISLAM, 2024)
History writing is an important part of human civilization. This article aims to uncover the process of writing history that took place in the Middle East region, which is a region very rich in civilization and historical information. The author uses qualitative research methods by relying on references related to the topic of historical historiography in the Middle East region. From this research, the author found that the development of historiography in the Middle East began with the process of recording in the form of inscriptions, poems memorized and taught for generations, transmission of hadith, to history writinig in Islamic times in the hands of scholars such as Ibn Hisham, Ibn Kathir, Ibn Al-Atsir and so on. Furthermore, there is a process of digitizing historical sources in modern times. In general, the recording of history in the Middle East has gone through a long and systematic process, although there are still unrevealed gaps in the history of civilization in the Middle East. And there are also negative influences of colonization in the Middle East that have led to unbalanced historical narratives at some era in Middle Eastern history. This paper is an additional reference for researchers who want to explore the historiography and history of civilization in the Middle East.